Earthquake engineering : theory and implementation with the 2015 International Building Code - Armouti, Nazzal S. (2015)
This authoritative resource has been thoroughly revised and expanded to contain the latest earthquake-resistant engineering techniques and regulations conforming with the 2015 International Building Code.